2008
DOI: 10.1245/s10434-008-9992-0
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT Fusion Scan Enhances CT Staging in Patients with Pancreatic Neoplasms

Abstract: This study evaluated PET/CT in the initial work-up of patients with PN. PET/CT increased sensitivity (87%) for detection of metastatic disease when combined with standard CT. In invasive cancer, PET/CT changed the management in 11% of our patients. PET/CT should be considered in the initial work-up of patients with potentially resectable pancreatic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(93 citation statements)
references
References 19 publications
8
82
1
2
Order By: Relevance
“…Another study demonstrated that the sensitivity and specificity of FDG-PET/CT was 88% and 89%, respectively, in patients being assessed for pancreatic cancer and changed the management of six (11%) patients. 47 These patients were found to have extrapancreatic disease that prevented them from undergoing pancreatic resection. Another study assessed two groups of patients, a diagnosis and staging group and a screening group, for progressive or recurrent disease.…”
Section: Positron Emission Tomography/computed Tomography In Pancreatmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that the sensitivity and specificity of FDG-PET/CT was 88% and 89%, respectively, in patients being assessed for pancreatic cancer and changed the management of six (11%) patients. 47 These patients were found to have extrapancreatic disease that prevented them from undergoing pancreatic resection. Another study assessed two groups of patients, a diagnosis and staging group and a screening group, for progressive or recurrent disease.…”
Section: Positron Emission Tomography/computed Tomography In Pancreatmentioning
confidence: 99%
“…44,[46][47][48]78,79,84 The effect size with regard to change in management ranges from 41% to 10%. 44,[46][47][48]78,79,84 The largest study was a retrospective series of 285 patients over a period of 7 years. The addition of PET/CT changed management in 31 (10%) patients.…”
Section: Additional Analysesmentioning
confidence: 99%
“…Pancreatic cancer has mostly metastasized to liver and peritoneal cavities, supraclavicular lymph nodes have rarely affected with pancreatic cancer (24). Prevalance of supraclavicular metastasis from pancreas cancer was 1.9% -2.4% (23,24). There have isolated rare case reports regarding pancreatic cancer and supraclavicular lymph node metastasis (23,24).…”
Section: Discussionmentioning
confidence: 97%
“…For supraclavicular metastasis of urothelial cancer, there were no reported cases for curative neck dissection in the literature. Pancreatic cancer was the fourth common cancer related death in both men and women (23). Pancreatic cancer has mostly metastasized to liver and peritoneal cavities, supraclavicular lymph nodes have rarely affected with pancreatic cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…Other imaging modalities, such as positron emission tomography-computed tomography, have been shown to provide a complimentary role to MDCT and MRCP in the detection of extra-abdominal metastases [17]. Thus, they may play a crucial role in the preoperative work-up of locally advanced cancers, since the treatment options would sharply vary based on the positron emission tomography scan findings.…”
Section: Radiologymentioning
confidence: 99%